Plastic hinge relocation in reinforced concrete beam–column joint using carbon fiber–reinforced polymer. Issue 14 (October 2019) - Arowojolu, Olaniyi; Ibrahim, Ahmed; Rahman, Muhammad K; Al-Osta, Mohammed; Al-Gadhib, Ali H
Reinforced concrete buildings with moment-resisting frames comprising beam–column joints (without joint shear reinforcement) designed prior to introduction of seismic codes are shear deficient when subjected to seismic loading, thereby mostly fail in shear at the core of the beam–column joint. However, those designed to the new seismic codes may fail by flexural hinging at the interface of the beam–column joint due to the yielding of the beam reinforcement at the location of highest stress demand (usually the beam–column joint interface). The shear failure has been precluded through the provision of transverse reinforcement at the joint in new design and the use of carbon fiber–reinforced polymer retrofitting in old buildings. Plastic hinge formation at the interface of the beam–column joint is critical because of its penetration into the joint and its effect on bond deterioration. In this study, eight corner-external beam–column joint specimens of 1/3 scale of a typical moment-resisting frame, made without transverse reinforcement, were tested for monotonic and reversed cyclic test under displacement-controlled regime. The control specimens failed by flexural hinging at the beam–column joint interface. The experimental results have been validated using the finite element model. The specimens were retrofitted with unidirectional carbon fiber–reinforced polymer of different layers and different length. After retrofitting, the plastic hinge was relocated to the curtailment end of the carbon fiber–reinforced polymer. The relocation of the plastic hinge resulted in higher load capacity and ductility.